Non-Invasive Glucose Monitoring Using Open Electromagnetic Waveguides - Hofmann, Maximilian; Bloss, M.; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (EuMA European Microwave Conference, 2012)
This paper presents a novel approach towards noninvasive glucose measurement. The introduced concept is based on an electromagnetic (EM) wave transmission along blood vessels. Theoretical investigation of a TEM wave propagation through a aqueous glucose solution is shown. The concept was evaluated by a simplified demonstrator which consists of a dielectric covered TEM-Waveguide. A 3D field simulation of the structure has been performed with a glucose dependent Debye relaxation model. The EM waveguide was fabricated and measured with various glucose concentrations. A phase difference of 12 deg for a 500mg/dl variation in glucose concentration was measured at 20GHz.
elib2cris::1512001600,hofmann2012b